2008
DOI: 10.1186/1471-213x-8-16
|View full text |Cite
|
Sign up to set email alerts
|

Parthenogenetic activation of bovine oocytes using bovine and murine phospholipase C zeta

Abstract: Background: During natural fertilization, sperm fusion with the oocyte induces long lasting intracellular calcium oscillations which in turn are responsible for oocyte activation. PLCZ1 has been identified as the factor that the sperm delivers into the egg to induce such a response. We tested the hypothesis that PLCZ1 cRNA injection can be used to activate bovine oocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 50 publications
(67 reference statements)
4
73
0
Order By: Relevance
“…Since induction of 240 abnormally high frequent and/or prolonged calcium elevation may trigger premature termination of embryonic development [36], the additional activation stimuli better to mimic the mechanism induced during normal fertilization without affecting other oocytes metabolic pathway. Ooplasmic injection of a promising SOAF candidate, phospholipase C zeta or its cRNA [37] was applied as a more physiological approach, but complicated steps required for isolation of this substance or 245 preparation of its cRNA as well as difficulty to control the injected volumes make this method far from practical.…”
Section: Discussionmentioning
confidence: 99%
“…Since induction of 240 abnormally high frequent and/or prolonged calcium elevation may trigger premature termination of embryonic development [36], the additional activation stimuli better to mimic the mechanism induced during normal fertilization without affecting other oocytes metabolic pathway. Ooplasmic injection of a promising SOAF candidate, phospholipase C zeta or its cRNA [37] was applied as a more physiological approach, but complicated steps required for isolation of this substance or 245 preparation of its cRNA as well as difficulty to control the injected volumes make this method far from practical.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that PLCZ cRNA injection into bovine oocytes was able to induce long-lasting [Ca 2C ] i oscillations and IP 3 R-1 downregulation and that it supported high rates of parthenogenetic development to the blastocyst stage (Malcuit et al 2006b, Ross et al 2008b. In the present study, we compared in vitro development, gene expression patterns, and epigenetic modifications in SCNT embryos activated by PLCZ cRNA injection with embryos activated by chemical methods or produced by IVF.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that JMJD3 is translated to protein soon after fertilization and persists, with oscillations, until the blastocyst stage. This expression pattern corresponds in time and cellular location with the decrease of H3K27me3 in preimplantation embryos (36).…”
Section: Expression and Localization Of Jmjd3 Protein In Preimplantationmentioning
confidence: 99%